Characterization of the cyclic deformation behavior of simulated HAZs and other constituent microstructural regions of P91 steel weldment. (November 2022) - Mariappan, K.; Nagesha, A.; Vasudevan, M.; Bhaduri, A.K.
Highlights: Strain amplitude dependent fatigue behavior of the HAZs of P91 WJ was studied. FGHAZ showed better fatigue performance among the HAZs of P91 weldment. Dual phase, initially soft ICHAZ exhibited poor fatigue lives under LCF condition. Serrations in the hysteresis loops of ICHAZ revealed the occurrence of DSA at 550 °C. Extensive substructural recovery due to cyclic deformation lowered KAM distribution. Abstract: Low cycle fatigue tests were conducted on the weld metal, coarse grain heat-affected zone (CGHAZ), fine grain heat-affected zone (FGHAZ), inter-critical heat-affected zone (ICHAZ), base metal and the actual weldment of P91 steel at 550 °C using different strain amplitudes. The P91 weldment and its constituent microstructural regions exhibited typical continuous cyclic softening behavior. In the HAZs, the FGHAZ exhibited better fatigue behavior. The CGHAZ and ICHAZ showed higher fatigue lives at the lower and higher strain amplitudes, respectively. An empirical relationship was established for predicting the fatigue life of the weldment using weighted factors of all the constituent regions.